2006
DOI: 10.2169/internalmedicine.45.1555
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Japanese Restless Legs Syndrome Patients with Cabergoline: An Open Clinical Preliminary Trial

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The studies of ropinirole, [29][30][31][32][33][34][35][36][37][38][39][40][41] pramipexole, rotigotine, [74][75][76][77][78][79][80][81][82][83][84][85] pergolide [86][87][88][89][90][91][92][93][94] and cabergoline, [95][96][97][98][99][100][101] respectively, in the treatment of iRLS are summarised by Supplementary Tables 2, 3 All these studies comparing dopamine agonists with placebo showed a significant improvement in the severity of RLS (assessed with several scales, being the most frequently used the International RLS Study Group Scale), in the IRLS frequency of "responder" rates (improvement in >50 %), in the Clinical Global Impression Improvement (CGI-I) and Patient Global Impression Improvement (PGI-I), in the quality of life (QoL) and in polysomnographic (PSG) measurements.…”
Section: Dopamine Agonistsmentioning
confidence: 99%
“…The studies of ropinirole, [29][30][31][32][33][34][35][36][37][38][39][40][41] pramipexole, rotigotine, [74][75][76][77][78][79][80][81][82][83][84][85] pergolide [86][87][88][89][90][91][92][93][94] and cabergoline, [95][96][97][98][99][100][101] respectively, in the treatment of iRLS are summarised by Supplementary Tables 2, 3 All these studies comparing dopamine agonists with placebo showed a significant improvement in the severity of RLS (assessed with several scales, being the most frequently used the International RLS Study Group Scale), in the IRLS frequency of "responder" rates (improvement in >50 %), in the Clinical Global Impression Improvement (CGI-I) and Patient Global Impression Improvement (PGI-I), in the quality of life (QoL) and in polysomnographic (PSG) measurements.…”
Section: Dopamine Agonistsmentioning
confidence: 99%